Infections and vaccines in the etiology of antiphospholipid syndrome (2012)
Purpose of review: To present scientific evidence supporting the infectious origin for the antiphospholipid syndrome (APS) by molecular mimicry between pathogens, infection and vaccination with ?2-glycoprotein I (?2-GPI) molecule. Recent findings: APS is characterized by the presence of pathogenic autoantibodies against ?2-GPI. The infection etiology of APS was well established. Likewise, a link between vaccination such as tetanus toxoid may trigger antibodies targeting tetanus toxoid and ?2-GPI, due to molecular mimicry between the two molecules. During the years, the pathogenic potential of anti-tetanus toxoid antibodies cross reactive with ?2-GPI were found to be pathogenic in animal models, inducing experimental APS. Summary: Accumulated evidence supports that the presence of anti-?2-GPI antibodies is associated with a history of infections and the main mechanism to explain this correlation is molecular mimicry. The relationship between tetanus toxoid vaccination and APS reveals a novel view on the autoimmune/autoinflammatory syndrome induced by adjuvants (ASIA). © 2012 Wolters Kluwer Health